La ciudad en el cine mexicano: (1940-1980) cuatro décadas de nota roja y sociodrama nacional - González Moreno, Obed (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The following writing is taken from the study: “Police the red note and in the Mexican Cinema: Sociological note de100 Years of National Cinema”. I retake four chapters of the same to point the importance of Literature and the city within the vision of some film directors to express the reality of the Mexico of four decades and its importance in the development of the human relations in the large city; its myths and customs. I realise this edition to reflect the unknown Mexico that within Literature yes is very known; but that does not reflect in the society greater impression since part of the imagination of the author is created.